Vascular dysfunction and pathology: focus on mechanical forces. (29th June 2021) - Garoffolo, Gloria; Pesce, Maurizio
Abstract : The role of mechanical forces is emerging as a new player in the pathophysiologic programming of the cardiovascular system. The ability of the cells to 'sense' mechanical forces does not relate only to perception of movement or flow, as intended traditionally, but also to the biophysical properties of the extracellular matrix, the geometry of the tissues, and the force distribution inside them. This is also supported by the finding that cells can actively translate mechanical cues into discrete gene expression and epigenetic programming. In the present review, we will contextualize these new concepts in the vascular pathologic programming.